Inherited thrombophilia in women with poor aPL‐related obstetric history: prevalence and outcomes. Survey of 208 cases from the European Registry on Obstetric Antiphospholipid Syndrome cohort. (August 2016) - Alijotas‐Reig, Jaume; Ferrer‐Oliveras, Raquel; Esteve‐Valverde, Enrique; Ruffatti, Amelia; Tincani, Angela; Lefkou, Elmina; Bertero, Maria Tiziana; Espinosa, Gerard; Coloma, Emmanuel; de Carolis, Sara; Rovere‐Querini, Patrizia; Canti, Valentina; et al.
Abstract : Aim: To analyse the prevalence and effects of inherited thrombophilic disorders (ITD) on maternal–foetal outcomes in cases of antiphospholipid antibody related to obstetric complications. Methods: Women with obstetric complaints who tested positive for aPL and with inherited thrombophilia were prospectively and retrospectively included. Results: ITD data were available in 208 of 338: 147 had obstetric antiphospholipid syndrome (OAPS) and 61 aPL‐related obstetric morbidity (OMAPS). 24.1% had ITD. Laboratory categories I and IIa were more related to OAPS‐ITD and IIb and IIc to OMAPS‐ITD. No significant differences in obstetric complaints were observed. Regarding ITD carriers, treatment rates were higher in OAPS than in OMAPS for LMWH and LDA plus LMWH ( P =.002). Conclusion: Cases with aPL‐related OAPS/OMAPS showed no differences in maternal–foetal outcomes regardless of the presence of one ITD. Maternal thrombotic risk was low, with ITD‐positive cases included. Registry data concur with Sydney criteria, whereby aPL‐ITD‐positive patients are classified as having antiphospholipid syndrome.